2019
DOI: 10.1097/sla.0000000000002653
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Risk Factors for Anastomotic Failure in 1594 Patients Treated by Transanal Total Mesorectal Excision

Abstract: Large tumors in obese, diabetic male patients who smoke have the highest risk of anastomotic failure. Acknowledging such risk factors can guide appropriate consent and clinical decision-making that may reduce anastomotic-related morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
224
4
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(273 citation statements)
references
References 41 publications
37
224
4
8
Order By: Relevance
“…Similar to previous reports, the present study found a significant correlation between AS and AL, suggesting that AL and AS might have reciprocal consequences . This study also found that the male sex and narrow pelvis were independently associated with AL, in agreement with prospective, multi‐institutional studies showing that both were risk factors for AL . The lower sensitivity of APCT has been reported, whereas the clinical utility of WCE as a predictor of AL remains undetermined .…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous reports, the present study found a significant correlation between AS and AL, suggesting that AL and AS might have reciprocal consequences . This study also found that the male sex and narrow pelvis were independently associated with AL, in agreement with prospective, multi‐institutional studies showing that both were risk factors for AL . The lower sensitivity of APCT has been reported, whereas the clinical utility of WCE as a predictor of AL remains undetermined .…”
Section: Discussionsupporting
confidence: 92%
“…This study supports the use of a TaTME approach for rectal cancer resection, with comparable postoperative outcomes and pathological safety compared to other approaches. This is in line with recent evidence on TaTME delivery across Europe . The leak rate was higher than previously reported, at 12.9%, which at univariable level was significantly higher than other techniques.…”
Section: Discussionsupporting
confidence: 92%
“…as well as of Penna et al . who reported successful non‐operative treatment of AL in 73% and 82%, respectively . Furthermore, anastomosis‐preserving management of AL was achieved in six patients in the AL group (75%), which may be considered as promising especially for AL in comparison to reported permanent stoma rates in up to 56%–68% of patients with AL .…”
Section: Discussionmentioning
confidence: 92%